ROLE PLAYING TECHNIQUE IN BUILDING STUDENTS’ MOTIVATION IN LEARNING ENGLISH - marhatin, ranis (LP3MKIL, 2023)
This article to know the benefit of teaching English by role playing technique for English Foreign Language Learner. This research designed in qualitative approach with library research method. The collecting data by using documenter of article and book both online and printing. The result that Learning English for EFL learners is crucial for personal, academic, and professional growth. It fosters global citizenship, cultural understanding, and innovation, enabling sustainable development. The role-playing technique fosters student motivation and engagement, fostering a dynamic learning environment. Embracing innovative strategies like role-playing helps educators create active, motivated, and empathetic learners ready for the 21st century.